Child labour a precarious future - Gomango, S P (Delhi Authors Press, 2001)
This publication aims to highlights the conditions of child workers and suggests possibles measures as well as legel remedies to their conditions of child workers.By emphasising that childern as the would be citizens of tomorrow should get a free,fearless
Keywords: Children-Employment; Age and employment; Children-Employment-Laws and legislation; Labor-Laws and legislation